PENGEMBANGAN KAWASAN BUDIDAYA JAGUNG UNTUK PENINGKATAN PEREKONOMIAN KABUPATEN PEMALANG - Eko Fitriono Harimurti; Khursatul Munibah; Untung Sudadi (TATALOKA, 2018)
Pemalang Regency had low economic rate, based on agriculture sector especially food crop sub-sector with Paddy and Maize as main contributor, had a high paddy fields conversion wich decreased the economic rate through Paddy production decreasement. The main objective of this research were to compose the Maize cultivation area development planning for Pemalang Regency economy improvement. The method used in this research were: mapping the Maize cultivation existing area, land suitability and availability evaluation, analysis of economic, marketing and correlation between Maize production with GDP growth and employment absorption. The results showed that there were about 1,804 ha of exsisting Maize cultivation area and 4,276 ha marginally suitable (S3) potential land. The Maize development were be feasible to be continued. Best benifit obtained from the channel that composed by Farmer-Depot-Industry, it gave lowest margin and highest farmer's share. The Maize market in integrated condition. Allocation potential land and 285.66 ha of Perhutani’s area predicted gave 5.94% of agriculture sector increasement and absorb all unemployment in Pemalang Regency.